2015
DOI: 10.1080/15226514.2015.1058336
|View full text |Cite
|
Sign up to set email alerts
|

Weeds ability to phytoremediate cadmium-contaminated soil

Abstract: An alternative method to other technologies to clean up the soil, air and water pollution by heavy metals is phytoremediation. Therefore, a pot culture experiment was conducted at the College of Agriculture, Ferdowsi University of Mashhad, Mashhad, Iran, in 2014 to determine the potential absorption of cadmium by Portulaca oleracea (Common purslane), Solanum nigrum (Black nightshade), Abutilon theophrasti (Velvetleaf) and Taraxacum officinale (Dandelion). The type of experiment was completely randomized design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Besides the accumulation of Na + and Cl − , there are reports regarding its ability to accumulate higher levels of K + in shoots in conditions of salt stress, reflected in the K + /Na + selectivity coefficients [39]. Due to its salt tolerance and edible properties purslane was regarded as a good candidate for soil desalinization [43,44], and given its potential in retaining toxic ions, also in heavy metals decontamination [45][46][47]. In a recent metabolomics study performed on two cultivars of purslane, 132 different metabolites were marked for their significant variation under salinity, notably an increase in proline and other amino acids, neutral and soluble sugars, sugar alcohols, amines, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the accumulation of Na + and Cl − , there are reports regarding its ability to accumulate higher levels of K + in shoots in conditions of salt stress, reflected in the K + /Na + selectivity coefficients [39]. Due to its salt tolerance and edible properties purslane was regarded as a good candidate for soil desalinization [43,44], and given its potential in retaining toxic ions, also in heavy metals decontamination [45][46][47]. In a recent metabolomics study performed on two cultivars of purslane, 132 different metabolites were marked for their significant variation under salinity, notably an increase in proline and other amino acids, neutral and soluble sugars, sugar alcohols, amines, etc.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only the highest soil Cd level (15 mg kg -1 soil) caused a noticeable reduction in root growth of C. erectus as compared to control treatment. Many previous studies (Wu et al, 2010;Bauddh and Singh, 2012;Abbasi et al, 2015;Hammami et al, 2016) reported reduction in growth of various plant species in response to Cd stress. Contrary to these findings, Manousaki and Kalogerakis Phytoremediation of Cd contaminated soils with tree species (2009) did not observe any significant effect of Cd on the root growth of Atriplex halimus and declared it as a Cd tolerant species.…”
Section: Discussionmentioning
confidence: 99%
“…A third approach has emerged over the past decade to solve the problems of pollution with heavy metals and organic components of wastewater of various sources. Recent works (Glick 2014;Hanin et al 2016;Al-Thani and Yasseen 2018a, 2018bYan et al 2020) have suggested such an approach as an environmentally friendly biological solution for many problems facing the ecosystem and human life in health, agriculture, and economy. Some important facts have emerged from the huge number of published articles about the cooperation between plants and associated microbes in dealing with harsh environmental issues: (1) Efficient phytoremediation actions always come from the cooperation of plants and associated microorganisms by beneficial interactions (Yasseen and Al-Thani 2013;Singh et al 2016;Ojuederie and Babalola 2017), as such combined actions could confer adaptability to harsh environments of drought, salinity, and possibly pollution stresses (Al-Qurainy and Abdel-Megeed 2009; Yasseen et al 2018); (2) Many mechanisms have been adopted by microorganisms to mitigate harsh abiotic stresses facing plants in general and crops in particular, the details of these mechanisms were discussed recently by Al-Thani and Yasseen (2018a); (3) Horizontal gene transfer (HGT) is possible between microorganisms and plants, this could lead to mutual beneficial activities and boosts the ecosystem to deal with harsh environment (Rosewich and Kistler 2000;Bode and M€ uller 2003;Al-Thani and Yasseen 2018b); (4) Plants might secrete exudates at the rhizosphere to stimulate and accelerate some metabolic pathways in microorganisms leading to degradation of petroleum hydrocarbons and/or immobilization of heavy metals (Chen et al 2017;Mishra et al 2017;Jin et al 2019);…”
Section: Biological Approachmentioning
confidence: 99%